Community Participation in the 2019 Legislative Elections in Kampar with Pekanbaru City - Jon Asmara, Candra; Rusdi, Rusdi (LPPM Universitas Ekasakti, 2024)
During the 2019 Legislative Election, the community living on the Kampar Regency-Pekanbaru City border showed low political participation, especially in legislative elections. Normatively, residents of this border area should have been able to vote for representatives in the Kampar Regency DPRD, but many could not due to lacking Kampar Regency ID cards. This study aims to describe community participation during the 2019 Legislative Election in this border area and the efforts made by the KPU to increase participation. Using a qualitative approach, the study found that community participation was generally apathetic. Many residents were not registered in the Permanent Voter List (DPT) as they neglected to update their ID cards. Efforts to enhance participation included free population administration services facilitated by village governments. Key stakeholders—village heads, the Kampar Regency KPU, the District Election Committee, and political actors—played roles in these efforts, with village heads proving the most influential in encouraging participation. Most residents in the border area are migrants living in housing complexes or apartments, with their population administration still linked to their original hometowns. Despite these challenges, the measures taken aimed to ensure greater inclusion in the electoral process, emphasizing the importance of administrative reforms to support democratic participation in the region.